The rapture or, The book of sleep - Iʿtimād as-Salṭana, Muḥammad Ḥasan Ibn-ʿAlī 1843-1896 (Mazda Publishers, 2016)
The text is in a style of dissident writing in the 19th century that creates a framework for criticism of the government and figures therein. The author wrote many historical works and was a person who was at the center of Iranian government. Here, he provides descriptions of personalities and events during the second half of the 19th century in Iran by inserting historical personalities and facts into a fantastical framework
Keywords: Nāṣir al-Dīn Shāh / Shah of Iran / 1831-1896; Iʿtimād as-Salṭana, Muḥammad Ḥasan Ibn-ʿAlī -- 1843-1896; Geschichte 1800-1900; Qajar Dynasty (Iran); Geschichte; Ausgabe -- Druckwerk; Iran / History / Qajar dynasty, 1794-1925; Iran; Fiktionale Darstellung